POLA DISTRIBUSI, POPULASI DAN AKTIVITAS HARIAN RUSA TIMOR (Cervus timorensis, de Blainville 1822) DI TAMAN NASIONAL BALI BARAT (Distribution, Population and Daily Activities of Timor Deer - Cervus timorensis,de Blainville 1822 in Bali Barat National Park) - Burhanuddin Masyud; Ricky Wijaya; Irawan Budi Santosa (Department of Forest Resources Conservation and Ecotourism - IPB University, 2007)
Study was carried out to know pattern of population distribution, population size and dailly activities of timor deer (Cervus timorensis, de Blainville 1822) in Bali Barat National Park. The result showed that pattern of population distribution of timor deer were not similar and tend to group based on food and water distribution. There were 23 population groups of timor deer i.e 12 groups at season forest and 11 groups at savanna forest. Total population numbere were 713-1320 heads i.e. fawns are 28 % and adult are 72 %, and sex ratio are 9:4. Time allocation for dailly activities of timor deer in Tanjung Sari grazing area were used for ingesti (52,05 %), resting (30,61 %), moving (6,21 %), investigating (6,12 %) and grroming (5.10 %). Relatively, the study also found different of time allocation for each dailly activities between male and female of timor deer.Key Words: Timor deer, distribution pattern, population size, daily behavior, national park.